Weathering the Storm : Independent Writing Programs in the Age of Fiscal Austerity. - Matzen Jr., Richard N.; Abraham, Matthew (Chicago : Utah State University Press, 2019)
"Assesses the socio-economic and political conditions that surrounded the rise of independent writing programs since the 2008 financial collapse. Looking at institutional conditions and challenges programs have faced in the last ten years as they struggled to stake their turf in a rapidly changing educational environment"--Provided by publisher.
13. Becoming a Social Fact: Weathering the 2008 Financial Crisis at the University of Pennsylvania / Valerie Ross, Patrick Wehner, and Rodger LeGrand14. Making a Place for Writing Studies in a Crowded Institutional Landscape / Frank Gaughan; About the Authors; Index
Print version record.
Includes bibliographical references and index.
JSTOR
Keywords: English language -- Rhetoric -- Study and teaching (Higher) -- Economic aspects -- United States; English language -- Rhetoric -- Study and teaching (Higher) -- Political aspects -- United States; Writing centers -- Economic aspects -- United States; Writing centers -- Political aspects -- United States; Education, Higher -- Economic aspects -- United States; Global Financial Crisis, 2008-2009.; Centres de communication écrite -- Aspect économique -- États-Unis.; Centres de communication écrite -- Aspect politique -- États-Unis.; Enseignement supérieur -- Aspect économique -- États-Unis.; Crise financière mondiale, 2008-2009.; LANGUAGE ARTS & DISCIPLINES / General; Education, Higher -- Economic aspects; United States; 2008-2009; Electronic books